Metamorphosis eaudiobook - Kafka, Franz (Naxos AudioBooks, 2005)
Gregor Samsa wakes up one morning to find he has been transformed into a gigantic insect. This extraordinary tale of imagination was written by Kafka against the backdrop of increasing turmoil in central Europe and remains not just an affecting tale but a disturbing allegory. It is read here, in a new translation, by master story teller Martin Jarvis.